Is Cardiovascular Reactivity Associated With Atherosclerosis Among Hypertensives? - Gianaros, Peter J. (Hypertension, 2002)
Exaggerated cardiovascular reactivity to behavioral challenges among otherwise healthy individuals has been associated with carotid atherosclerosis. We evaluated whether a similar relationship exists among hypertensives, who are at a heightened atherosclerotic risk. Untreated, hypertensive men (n=251; age range, 40 to 70 years; 197 white, 54 black) completed a standardized battery of behavioral challenges while their blood pressure responses to the battery were measured. Mean and maximum carotid intima-media thickness and the occurrence of carotid plaques were subsequently determined using B-mode ultrasonography. Although greater systolic and diastolic responses to the battery were associated with greater mean and maximum intima-media thickness in univariate analyses (P<0.01), only diastolic reactivity showed a unique association with mean and maximum carotid intima-media thickness after multivariate adjustment for age, race, socioeconomic status, smoking and alcohol use, body mass index, lipid profile, glucose and insulin concentrations, and resting blood pressure (P<0.05). Carotid plaque occurrence was associated with greater systolic reactivity (P=0.05) and was marginally associated with greater diastolic reactivity (P=0.07) in univariate analyses, but neither systolic nor diastolic reactivity was uniquely associated with the presence of carotid plaques after multivariate risk-factor adjustment. Among hypertensives, exaggerated behaviorally evoked cardiovascular reactivity appears to be uniquely associated with greater carotid intima-media thickness but not with carotid plaque occurrence.